Immune Regulation of Tissue Repair and Regeneration via miRNAs—New Therapeutic Target - Piotto, Celeste; Julier, Ziad; Martino, Mikaël M. (Frontiers in Bioengineering and Biotechnology, 2018)
The importance of immunity in tissue repair and regeneration is now evident. Thus, promoting tissue healing through immune modulation is a growing and promising field. Targeting microRNAs (miRNAs) is an appealing option since they regulate immunity through post-transcriptional gene fine-tuning in immune cells. Indeed, miRNAs are involved in inflammation as well as in its resolution by controlling immune cell phenotypes and functions. In this review, we first discuss the immunoregulatory role of miRNAs during the restoration of tissue homeostasis after injury, focusing mainly on neutrophils, macrophages and T lymphocytes. As tissue examples, we present the immunoregulatory function of miRNAs during the repair and regeneration of the heart, skeletal muscles, skin, and liver. Secondly, we discuss recent technological advances for designing therapeutic strategies which target miRNAs. Specifically, we highlight the possible use of miRNAs and anti-miRNAs for promoting tissue regeneration via modulation of the immune system.